2021
DOI: 10.4038/sljss.v44i1.7953
|View full text |Cite
|
Sign up to set email alerts
|

Public debt, budget deficit and tax policy reforms for fiscal consolidation in Sri Lanka: rationale and feasibility

Abstract: This paper aims to examine the rationale and feasibility to minimise the budget deficit that maintains the public debt at manageable level without retarding economic growth. Accumulation of government debt may subsequently shape future budget deficit via policies aimed at deficit reduction. Government authorities substantiate austerity and deficit reduction arguing for a case of sustainable fiscal policy. Hence, this study investigates the relationship between public debt, budget deficit and tax policy reforms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 2 publications
3
8
0
Order By: Relevance
“…The cointegration results are consistent with prior expectations and other studies' findings that examined public debt, budget deficit, and tax policy reforms for fiscal consolidation in Sri Lanka [10]. In their study [10], they found a positive and statistically significant relationship between public debt and taxation. Additionally, other studies analyzed the relationship between taxation and inflation in Nigeria [9].…”
Section: Findings and Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The cointegration results are consistent with prior expectations and other studies' findings that examined public debt, budget deficit, and tax policy reforms for fiscal consolidation in Sri Lanka [10]. In their study [10], they found a positive and statistically significant relationship between public debt and taxation. Additionally, other studies analyzed the relationship between taxation and inflation in Nigeria [9].…”
Section: Findings and Discussionsupporting
confidence: 90%
“…There was an examination of public debt, budget deficit, and tax policy reforms for fiscal consolidation in Sri Lanka that employed the Vector Error Correction model (VECM) [10]. It was revealed that direct government tax revenue, indirect tax revenue, and consumer price index are negatively correlated with government debt to GDP ratio in the long run.…”
Section: Empirical Literaturementioning
confidence: 99%
See 3 more Smart Citations